2022
DOI: 10.2147/ppa.s376000
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Clinical Guidelines on STATIN Prescribing Among Diabetic Patients Aged 40–75 Years Old in a Primary Care Setting: A Cross-Sectional Study

Abstract: Background Diabetes mellitus (D.M.) is a chronic metabolic disease caused by decreased insulin secretion, which increases the risk of cardiovascular diseases. Evidence has shown that statins reduce cardiovascular risk in patients with diabetes; moreover, most clinical guidelines recommend statins. Objective This study aimed to assess the level and status of adherence to guidelines on statin prescription in patients with diabetes mellitus in a primary care setting in Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…The study by Nelson et al (2021) found the proportion of female patients on appropriate statin pharmacotherapy to be 31.4%, whereas the proportion of male patients was 68.6%. Although Abukhalil et al (2022) did not find the same gender skew, they did find that those with known ASCVD were significantly more likely to be prescribed a statin than those who would benefit from preventative use as outlined in the ADA guidelines.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…The study by Nelson et al (2021) found the proportion of female patients on appropriate statin pharmacotherapy to be 31.4%, whereas the proportion of male patients was 68.6%. Although Abukhalil et al (2022) did not find the same gender skew, they did find that those with known ASCVD were significantly more likely to be prescribed a statin than those who would benefit from preventative use as outlined in the ADA guidelines.…”
Section: Resultsmentioning
confidence: 80%
“…Significant socioeconomic and geographic variations existed between populations studied, yet the lack of consistent ADA guideline adherence by providers to statin prescription persisted across studies. Abukhalil et al (2022) found that provider adherence to statin prescribing was 74%, whereas Eder et al (2019) found that number closer to 60.5%. Garza et al (2017) was closer to 55.1%.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations